2012
DOI: 10.1016/j.breast.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and fine needle aspiration cytology of axillary lymph nodes in breast cancer. To do or not to do?

Abstract: 106/429 (24.7%) Node-positive axillae were identified by ultrasound-guided FNAC and spared unnecessary sentinel node biopsy. Unfortunately, the percentage of false negative results of ultrasound-guided FNAC (28.1%, 323/1150) was very high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 36 publications
8
61
1
Order By: Relevance
“…Tahir et al (2008) reported an increase in sensitivity from 47.1% to 80% when two or more nodal metastases were found. Sensitivity, on the other hand, was lower for US 1 FNAC than for US alone, as also reported in the literature (Leenders et al 2012;Park et al 2011).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Tahir et al (2008) reported an increase in sensitivity from 47.1% to 80% when two or more nodal metastases were found. Sensitivity, on the other hand, was lower for US 1 FNAC than for US alone, as also reported in the literature (Leenders et al 2012;Park et al 2011).…”
Section: Discussionsupporting
confidence: 62%
“…There are a number of reasons for this discrepancy. First, the prevalence of axillary metastases in the study populations differs greatly, ranging between 25% and 58% (Leenders et al 2012). In our study, the prevalence of nodal metastases was 28.4%, which is relatively low compared with values in the literature.…”
Section: Discussioncontrasting
confidence: 62%
“…With the availability of Ax US & SLNB techniques, ability to gather this information peri-operatively has improved greatly [16]. Leenders et al (2012) reported sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of axillary ultrasound alone as 43.8 % (188/429), 80.7 % (582/721), 57.5 % (188/327) and 70.7 % (582/823), respectively. They also reported sensitivity, specificity, PPV, NPV of Ax US + FNAC as 24.7 % (106/429), 99.9 % (720/ 721), 99.1 % (106/107) and 69.0 % (720/1043) respectively [17].…”
Section: Discussionmentioning
confidence: 99%
“…Leenders et al (2012) reported sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of axillary ultrasound alone as 43.8 % (188/429), 80.7 % (582/721), 57.5 % (188/327) and 70.7 % (582/823), respectively. They also reported sensitivity, specificity, PPV, NPV of Ax US + FNAC as 24.7 % (106/429), 99.9 % (720/ 721), 99.1 % (106/107) and 69.0 % (720/1043) respectively [17]. Similarly Fernandez et al (2012) found that when compared with final axillary histology, ultrasound fine-needle aspiration showed positive predictive value of 87 %, negative predictive value of 82 %, sensitivity of 53 % and specificity of 100 % [12].…”
Section: Discussionmentioning
confidence: 99%
“…Further it is possible that small metastases not previously identified by standard histopathology may be detected. Previous work has demonstrated that increasing interrogation of lymph nodes, histologically, using a 2 mm step sectioning protocol upstaged between 7% and 42% of cases when compared to a single section and that the use of OSNA increases the rate of detection of micro-metastases [7] [8].…”
Section: Introductionmentioning
confidence: 99%